2016
DOI: 10.1155/2016/3191089
|View full text |Cite
|
Sign up to set email alerts
|

An Unexpected Interaction between Sofosbuvir/Ledipasvir and Atorvastatin and Colchicine Causing Rhabdomyolysis in a Patient with Impaired Renal Function

Abstract: Hepatitis C virus (HCV) infection affects roughly 170 million people worldwide. Sofosbuvir/Ledipasvir (Sof/Led) is a new once daily direct acting antiviral combination pill that was approved in October 2014 for use in patients with HCV genotype 1 infection. Coadministration of Sof/Led is studied only with rosuvastatin which shows significantly increased level of drug and is associated with increased risk of myopathy, including rhabdomyolysis. There is no mention of such HMG-CoA reductase inhibitor interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(47 citation statements)
references
References 6 publications
3
44
0
Order By: Relevance
“… NEUSS 1986 [ 44 ] Case report eGFR of 23 (serum creatinine of 2.3 mg/dL) Gout flare prophylaxis 0.6 mg PO twice daily (long term) 1 1 No gout flare during therapy, but with multi-organ failure, including AKI (serum creatinine peaked at 3 mg/dL). PATEL 2016 [ 46 ] Case report eGFR of 32 (serum creatinine of 1.87 mg/dL) Gout flare prophylaxis 0.6 mg PO once daily (for > 5 years) 1 1 Efficacy data not available. Renal function deteriorated (serum creatinine peaked at 2.5 mg/dL) but returned to baseline upon colchicine cessation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… NEUSS 1986 [ 44 ] Case report eGFR of 23 (serum creatinine of 2.3 mg/dL) Gout flare prophylaxis 0.6 mg PO twice daily (long term) 1 1 No gout flare during therapy, but with multi-organ failure, including AKI (serum creatinine peaked at 3 mg/dL). PATEL 2016 [ 46 ] Case report eGFR of 32 (serum creatinine of 1.87 mg/dL) Gout flare prophylaxis 0.6 mg PO once daily (for > 5 years) 1 1 Efficacy data not available. Renal function deteriorated (serum creatinine peaked at 2.5 mg/dL) but returned to baseline upon colchicine cessation.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 2325 studies of colchicine use were identified, as summarised in a PRISMA flowchart of the literature search (Supplementary Figure 1 ), and a final total of 49 studies were eligible for data extraction [ 9 57 ]. Twenty of these 49 studies, which were mostly case series or case reports, described the efficacy and/or safety outcomes of colchicine use stratified by renal function, as summarised in Tables 2 and 3 , respectively [ 17 , 18 , 20 , 22 , 24 , 28 , 29 , 31 33 , 35 – 37 , 39 , 44 , 46 , 49 , 53 , 55 , 57 ]. The remaining 29 studies reported efficacy and/or safety outcomes of colchicine use without renal function stratification, as summarised in Supplementary Table 2 and Supplementary Table 3 , respectively [ 9 16 , 19 , 21 , 23 , 25 27 , 30 , 34 , 38 , 40 43 , 45 , 47 , 48 , 50 – 52 , 54 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first reported case of likely colchicine‐induced rhabdomyolysis due to interaction with G/P. An additional case of rhabdomyolysis has been reported in a patient with renal dysfunction being treated with the NS5A inhibitor ledipasvir and NS5B polymerase inhibitor sofosbuvir while continuing colchicine and atorvastatin . Unlike the prior case, our patient had a dose reduction of colchicine before initiation of HCV therapy and was not taking a statin that may have increased the muscle toxicity.…”
Section: Hcv Rna Genotype 1 Ns5a Drug Resistance Panel Resultsmentioning
confidence: 69%
“…An additional case of rhabdomyolysis has been reported in a patient with renal dysfunction being treated with the NS5A inhibitor ledipasvir and NS5B polymerase inhibitor sofosbuvir while continuing colchicine and atorvastatin. 13 Unlike the prior case, our patient had a dose reduction of colchicine before initiation of HCV therapy and was not taking a statin that may have increased the muscle toxicity. Coadministration of colchicine and G/P is not prohibited, but this combination has not been studied.…”
mentioning
confidence: 80%